Pengaruh Modal Asing Terhadap Kemampuan Perusahaan Dalam Memperoleh Laba (Rentabilitas) (Students' Journal of Engineering, 2015)
Rentability of a company reflects the level of the company's efficiency in consuming their capital. Rentability is calculated by dividing the income without interest and tax with total active. The amount of the economical rentability is often proposed by the company's ability to work with all their capital to earn profit. To know further whether the use of foreign capital have a beneficial influence the rentability of their- own capital added by the foreign capital as well as if the use of the fund is influenced by their own capital.Key Words: Economical Rentability, Company Profits